O/C Isotopic and EPR Signature of Marble from the Apuan Alps (Italy): A Critical Review - Massimo Coli; Francesco Di Benedetto; Antonella Buccianti (Applied Sciences)
A critical review of studies concerning the attribution of the provenance of marble from the Apuan Alps (Italy) (AAM) used for historical–monumental buildings and artefacts is proposed based on its O/C isotopic and EPR signature. First, a summary of the geological origin of AAM and its geo-structural evolution and setting is presented. A review of the exploitation history of AAM is then discussed. This geological and historical information is used as categorical information to better constrain the literature multimethodic database, containing numerous data, including O/C isotopic and EPR spectroscopic parameters. A robust multivariate statistical analysis of the combination of all these data is performed. The results point to the fact that the O/C isotopic and EPR signature can help in attributing an analysed AAM sample to a marble extraction district, and to a certain extent also to a site, whereas the discrimination of the individual quarry appears to not yet be achievable.